Deconstructing Photospheric Spectral Lines in Solar and Stellar Flares - Monson, Aaron J.; Mathioudakis, Mihalis; Kowalski, Adam F. (The Astrophysical journal, 2024)
During solar flares, spectral lines formed in the photosphere have been shown to exhibit changes to their profiles despite the challenges of energy transfer to these depths. Recent work has shown that deep-forming spectral lines are subject to significant contributions from regions above the photosphere throughout the flaring period, resulting in a composite emergent intensity profile from multiple layers of the atmosphere. We employ radiative–hydrodynamic and radiative transfer calculations to simulate the response of the solar/stellar atmosphere to electron beam heating and synthesize spectral lines of Fe i to investigate the line-of-sight velocity fields information available from Doppler shifts of the emergent intensity profile. By utilizing the contribution function to deconstruct the line profile shape into its constituent sources, we show that variations in the line profiles are primarily caused by changes in the chromosphere. Up-flows in this region were found to create blueshifts or false redshifts in the line core dependent on the relative contribution of the chromosphere compared to the photosphere. In extreme solar and stellar flare scenarios featuring explosive chromospheric condensations, redshifted transient components can dominate the temporal evolution of the profile shape, requiring a tertiary component consideration to fully characterize. We conclude that deep-forming lines require a multicomponent understanding and treatment, with different regions of the spectral line being useful for probing individual regions of the atmosphere’s velocity flows.